Bank financing to SMEs in the Republic of North Macedonia: Evidence from survey data - Tanja Jakimova; Neda Popovska-Kamnar (National Bank of the Republic of North Macedonia, 2019)
This paper presents the main findings of the Survey for bank financing to small and medium enterprises (SMEs). The key objective was to capture the main features of the "supply side" of SMEs financing in the Republic of North Macedonia and to identify institutional and policy constraints of banks' involvement with SMEs. The findings reveal that banks considered SMEs lending market as large, competitive, not very saturated, but with very positive outlook. While the main driver for banks' involvement with SMEs sector is profitability and the good prospects of the SMEs segment, a number of obstacles are present, including SMEs-related factors, macroeconomic factors, legal and contractual environment and some bank-specific factors. The overall conclusion is that SMEs access to finance should be further supported and encouraged in order to increase their contribution to the growth of the economy.
Keywords: G20; 330; small and medium enterprises; bank finance; survey data